Efffects of general force characteristics on top speeds in cross-country skiing - Mikkola, J.; Laaksonen, M. S.; Holmberg, H. C.; Vesterinen, V.; Nummela, A. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Due to high racing speeds in cross-country skiing sprint (XCSS) the proportional use of V2 technique in free technique XCSS competitions is stressed. When using V2 technique most of the propulsive force is produced by upper body (Smith 2003) and therefore, the neuromuscular characteristics, especially in the upper body, are emphasized. To test neuromuscular and anaerobic abilities in runners, Rusko et al. (1993) have developed maximal anaerobic running test (MART), which have been later modified to XCS (Mikkola et al. 2007). The purpose of this study was to investigate the relationships between general force-velocity characteristics and sport specific speed as well as anaerobic performance when using V2 technique in XCS. Sixteen high level male XC skiers performed two sport specific tests on roller skies using V2 technique on a flat indoor tartan track: 30 m maximal skiing speed test (v30) and maximal anaerobic skiing test (MAST, 10 x 150 m with increasing speed / 100-s recovery). In MAST, the maximal velocity (vMAST) and maximal blood lactate concentration (LAmax) were determined. In addition, power (at 50% of 1RM) and maximal (1 RM) force production of lower and upper body by leg press (LP) and bench press (BP) were determined. Maximal isometric trunk extension (FTE) and flexion (FTF) forces were measured using a specific dynamometer. vMAST correlated strongest with the v30 (r = 0.84), FTF (r = 0.77) and 1 RM BP (r = 0.75) (p<0.001). Also BP power (r = 0.70, p<0.01) and FTE (r = 0.62, p<0.05) correlated significantly with vMAST. Respectively, the strong correlations between v30 and FTF (r = 0.84) and FTE (r = 0.83) (p<0.001) were observed. In addition, v30 correlated significantly with BP power (0.78, p<0.001) and BP 1RM (r = 0.64, p<0.01). Only weak, non-significant correlations between vMAST and LAmax (r = 0.15) as well as between LP variables and vMAST or v30 (r < 0.48) were observed. This study suggests that not only specific, but also general force-velocity characteristics, especially in trunk and upper body, are important determinants of maximal speed and anaerobic performance in V2 technique on flat terrain. The present results are in line the study of Stöggl et al. (2007) indicating the strong connection between XCSS performance and specific explosive strength and maximal power. Thus, neuromuscular characteristics of the upper body may be crucial especially in XCS sprint which includes short sprints and skier against skier actions. In addition, the present correlations between v30 and vMAST (strong) and between vMAST and LAmax (weak) indicate that in XCS neuromuscular and technical aspects may limit the top velocities (in MAST) more than metabolic characteristics.